Issues in Genre Analysis and Genre Evolution Within the Discursive and Social Practices - Olagunju, Sade (International Journal of Arts, Languages, Linguistics and Literary Studies, 2022)
The paper explains various ways by which discourse can be understood through genre analysis approach. It also sheds light on genre evolution while focusing on the diachronic study of language to show some gradual and continuous development in language studies over time. Some of the existing works on genre analysis are considered to further explicate the notion of genre analysis, genre evolution, hybrid genre and how genre and register are related linguistic properties. Genre analysis examines how texts are structured to fulfil communicative purposes and how members of a discourse community use genre to claim and attribute community memberships. Genre analysis examines the structure and communicative purpose of different types of texts (e.g business letters, newspaper editorials, weblogs) and the way these texts function among the groups of people who use them. Martins (1984) and Eggins (1994) link genre to context of culture and explain that genre are realised through language. This means we only know we have a particular genre by looking at the way language gets used. The study of this nature will serve as resourceful material for linguistic scholars.